1995
DOI: 10.1037/1040-3590.7.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Multimethod assessment of covert antisocial behavior in children: Laboratory observations, adult ratings, and child self-report.

Abstract: Given the high risk for delinquency of children with attention-deficit hyperactivity disorder (ADHD), their display of covert or clandestine antisocial behavior is important developmentally and theoretically. In a laboratory probe of the temptation to (a) steal small amounts of money and desired objects, (b) destroy property, and (c) use an answer key to cheat on a worksheet, counts of these covert behaviors were reliably made. Laboratory property destruction was highly correlated with parallel naturalistic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…During the summer research program, we also investigated ADHD children's responses to methylphenidate. Other research utilizing this sample is reported in Anderson, Hinshaw, and Simmel (1994); Hinshaw, Simmel, and Heller (1995);and Nigg, Swanson, and Hinshaw (1996).…”
Section: Methodsmentioning
confidence: 86%
“…During the summer research program, we also investigated ADHD children's responses to methylphenidate. Other research utilizing this sample is reported in Anderson, Hinshaw, and Simmel (1994); Hinshaw, Simmel, and Heller (1995);and Nigg, Swanson, and Hinshaw (1996).…”
Section: Methodsmentioning
confidence: 86%
“…Multiple informant data are preferable to increase reliability and validity and to capture average behavior across contexts, yet specific informants may be considered more valid for particular symptoms and settings. Self-reports are important sources for internalized symptoms, such as depression, and covert CP (Hinshaw, Simmel, & Heller, 1995), whereas teachers might be the best reporters for overt CP because they have access to a greater range of comparison youth (Stanger & Lewis, 1993). Finally, many studies of symptom patterns have involved small clinical samples, which tend to overestimate prevalence and prevent generalization to community populations (Angold & Costello, 1993).…”
Section: Methodological Issues In Assessing Symptomatology Patternsmentioning
confidence: 98%
“…The experimenter was then called out of the room and left the answer key near where the boys were working. This situation was based on one developed by Hinshaw, Simmel, and Heller (1993) to assess covert antisocial behavior. After 12 min, the experimenter returned and, without checking the boysÕ answers, told the boys that they would both receive a prize to thank them for their help with the project.…”
Section: Methodsmentioning
confidence: 99%